The 4Ds of Dealing With Distress – Distract, Dilute, Develop, and Discover: An Ultra-Brief Intervention for Occupational and Academic Stress - Mansell, Warren; Urmson, Rebecca; Mansell, Louise (Frontiers in Psychology, 2020)
The Covid-19 crisis has clarified the demand for an ultra-brief single-session, online, theory-led, empirically supported, psychological intervention for managing stress and improving well-being, especially for people within organisational settings. We designed and delivered ‘4Ds for Dealing with Distress’ during the crisis to address this need. 4Ds unifies a spectrum of familiar emotion regulation strategies, resilience exercises, and problem-solving approaches using perceptual control theory and distils them into a simple four-component rubric (Distract – Dilute – Develop – Discover). In essence, the aim is to reduce distress and restore wellbeing, both in the present moment through current actions (distract or dilute), and through expressing longer-term goal conflicts (e.g. through talking, writing, and drawing) to discover new perspectives that arise spontaneously after sufficient time and consideration. The intervention is user-led in that it draws on users’ own idiosyncratic and pre-existing experiences, knowledge, skills and resources to help them apply an approach, or combination of approaches, that are proportionate and timed to the nature and context of the stress they are experiencing. In this article we review the empirical basis of the approach within experimental, social, biological and clinical psychology, illustrate the novel and time-efficient delivery format, describe its relevance to sports and exercise, summarise feedback from the recipients of the intervention to date, and describe the directions for future evaluation.